2010
DOI: 10.1007/s12573-011-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the distribution of collagen fiber recruitment

Abstract: The passive biomechanical behavior of blood vessels is generally modeled by a parallel arrangement of elastin and collagen, with collagen recruitment depending on vessel strain. We experimentally determined the collagen recruitment distribution using confocal microscopy. Digital images from sections of rabbit carotid artery under increasing circumferential stretch ratio were acquired. The straightness of the fibers was measured to compute the fraction of recruited fibers for each stretch ratio. The experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…The aforementioned experimental findings enhanced the first generation of structural models based on the definition of a strain energy function, which considered the arterial wall as a soft matrix material reinforced by variously distributed fibers families [24,58,25,19], with the addition of a fiber activation stretch or of a probability distribution function, accounting for gradual recruitment at finite strain [42,23]. All these models assume an affine deformation of the collagen network, as experimentally evidenced by several contributions [43,52], i.e.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The aforementioned experimental findings enhanced the first generation of structural models based on the definition of a strain energy function, which considered the arterial wall as a soft matrix material reinforced by variously distributed fibers families [24,58,25,19], with the addition of a fiber activation stretch or of a probability distribution function, accounting for gradual recruitment at finite strain [42,23]. All these models assume an affine deformation of the collagen network, as experimentally evidenced by several contributions [43,52], i.e.…”
Section: Introductionmentioning
confidence: 85%
“…3 (a1) and (a2)), revealing optimal in-plan morphology. In fact, previous studies have investigated the transmural angle (radial direction) of the fibers and showed that it is negligible in comparison to the in-plane angle [42,41,44]. As a result, although the negligible transmurality information is lost, the fibers are represented with maximal effective length, strongly improving the interpretation of their in-plane orientation.…”
Section: Image Analysis and Characterization Of Fiber Kinematicsmentioning
confidence: 99%
“…In addition, the undulation parameters of medial collagen were set to k M min ¼ 1:0 and k M max ¼ 1:1 according to Ref. [40] for rabbit aortas. The relatively low medial collagen undulation has also been observed in humans [56].…”
Section: Parameter Identificationmentioning
confidence: 99%
“…4.6) and align obliquely to the circumferential direction [9], while elastic fibers are straight, and thus, the incremental elastic modulus is low (Table 4.1). In high-pressure region, stiff collagen fibers become straight and begin to be stretched [10], resulting in the strain hardening of the blood vessel wall. Since collagen fibers are not stretched in low-pressure region, breaking strain of the aorta (~100 %) is in Mean ± SEM, n = 16…”
Section: Large Deformation and Nonlinear Mechanical Propertiesmentioning
confidence: 99%